2003
DOI: 10.1590/s0100-879x2003001000024
|View full text |Cite
|
Sign up to set email alerts
|

The 5alpha-reductase type 1, but not type 2, gene is expressed in anagen hairs plucked from the vertex area of the scalp of hirsute women and normal individuals

Abstract: The aim of the present study was to determine the expression of the genes for type 1 (SDR5A1) and type 2 (SDR5A2) 5α-reductase isoenzymes in scalp hairs plucked from 33 hirsute patients (20 with polycystic ovary syndrome and 13 with idiopathic hirsutism) and compare it with that of 10 men and 15 normal women. SDR5A1 and SDR5A2 expression was estimated by RT-PCR using the gene of the ubiquitously expressed protein ß 2 -microglobulin as an internal control. The results are expressed as arbitrary units in relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
0
7
1
Order By: Relevance
“…There are several differences in study design that can explain the contrast between our results and those of Oliveira et al (13). They analyzed SRD5A expression in plucked anagen hairs but not in the connective tissue sheath, the lower bulb, the dermal papilla cells, and the sebaceous gland; we isolated the dermal papillae.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…There are several differences in study design that can explain the contrast between our results and those of Oliveira et al (13). They analyzed SRD5A expression in plucked anagen hairs but not in the connective tissue sheath, the lower bulb, the dermal papilla cells, and the sebaceous gland; we isolated the dermal papillae.…”
Section: Discussioncontrasting
confidence: 56%
“…Previously, Sultan et al (12) and Oliveira et al (13) used RT-PCR to investigate SRD5A1 and SRD5A2 expression in plucked scalp hairs from hirsute patients (13 idiopathic and 20 with PCOS) and controls (10 men and 15 nonhirsute women). Their study did not detect SRD5A2 expression in hair samples and found no differences in SRD5A1 expression between any of the groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, some studies already investigated mRNA expression of sex steroid biosynthesis enzymes in different androgen-dependent tissues from healthy humans and also from patients with different diseases [English et al, 2000;Kim et al, 2002;Provost et al, 2002;Blouin et al, 2003;Labrie et al, 2003;Oduwole et al, 2003;Oliveira et al, 2003;Quinkler et al, 2003Quinkler et al, , 2004Stoffel-Wagner, 2003]. This includes reproductive dysfunction and polycystic ovary syndrome (PCOS) and also various malignancies [Koh et al, 2002;Gunnarsson et al, 2003;Labrie et al, 2003;Vihko et al, 2003].…”
mentioning
confidence: 99%
“…Androgenic alopecia in humans involves DHT production from local activity of 5α‐reductase isoenzymes in the skin of affected areas . We have shown for the first time, to the best of the authors' knowledge, that 5αR1 and 5αR3 – but not 5αR2 – are expressed in the skin of healthy dogs.…”
Section: Discussionmentioning
confidence: 79%